Multifocal Tuberculous Spondylitis and Extensive Extraspinal Tubercular Osteomyelitis without Immunocompromise: Case Report and Literature Review - Tomer, Divya; Bartakke, Girishchandra; Khose, Shrikant (Asian Journal of Neurosurgery, 2023)
Multifocal extensive spinal and extraspinal tuberculosis is very rare. So far, fewer than 10 cases have been reported. We hereby report two such cases to highlight their rarity, the diagnostic and therapeutic challenges they presented, and the overall prognosis of the condition. The two patients (a 19-year-old woman and another 20-year-old woman) had multifocal extensive tuberculosis involving spine and appendicular skeleton with neurological deficit. Both patients presented with back and neck pain and gradual neurological deficit. The insidious onset and malignancy-like spread pattern mimicked neoplasm. After thorough investigations with magnetic resonance imaging, positron emission tomography scan, and biopsy, antitubercular drug therapy was started, and debridement and fixation were done for significant thoracic and cervical vertebral lesions, respectively. Both patients showed excellent neurological recovery after the procedure. Early surgical treatment of the cases with large abscesses helped provide decompression and stabilization and prevented neurological deterioration and deformity. In patients with noncontiguous spinal tuberculosis, high percentage of surgical treatment may be required due to the aggressive behavior of the disease.
Keywords: multifocal tuberculosis; skipped lesions; extraspinal tuberculosis; tubercular spondylitis; skeletal tuberculosis